IMPLEMENTASI KEBIJAKAN PERATURAN PEMERINTAH NO 23 TAHUN 2021 TENTANG PENYELENGGARAAN KEHUTANAN DI BALAI KESATUAN PENGELOLAAN HUTAN (KPH) BATULANTE KABUPATEN SUMBAWA - Aldi Apriansyah, (Nusantara Hasana Journal, 2025)
Government Regulation No. 23 of 2021 concerning Forestry Implementation aims to regulate issues of Rehabilitation, Security, and Community Empowerment. Articles such as Article 1 paragraphs 50 and 56, for example, explain the nursery, seeding, and planting systems, even regulating reforestation. Even paragraphs 73-76 discuss forest security. This study uses a descriptive qualitative research method and data collection techniques using observation, interviews, and documentation. This study uses Edward III's policy implementation theory, which in this theory there are four indicators that determine the success of a policy. These four indicators are Communication, Resources, Disposition, and Bureaucratic Structure. The conclusion of this study is about how the Batulanteh Forest Management Unit (KPH Batulanteh) works optimally despite experiencing several obstacles, especially related to resources such as budget, implementers, and infrastructure.